2010
DOI: 10.3109/14764172.2010.502456
|View full text |Cite
|
Sign up to set email alerts
|

Keratosis pilaris atrophicans: Treatment with intense pulsed light in four patients

Abstract: Our results suggest IPL should be considered as a safe treatment option in patients with KPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Rodriguez‐Lojo and colleagues treated keratosis pilaris atrophicans in four patients in five to nine sessions and observed clinical improvement between 75% and 100%. The effect was sustained during a 10‐month follow‐up period . In a prospective right–left controlled trial involving 18 patients, Highton and colleagues demonstrated statistically significant improvement in hidradenitis suppurativa over a 12‐month period (level 2a evidence) .…”
Section: Results By Diseasementioning
confidence: 94%
See 3 more Smart Citations
“…Rodriguez‐Lojo and colleagues treated keratosis pilaris atrophicans in four patients in five to nine sessions and observed clinical improvement between 75% and 100%. The effect was sustained during a 10‐month follow‐up period . In a prospective right–left controlled trial involving 18 patients, Highton and colleagues demonstrated statistically significant improvement in hidradenitis suppurativa over a 12‐month period (level 2a evidence) .…”
Section: Results By Diseasementioning
confidence: 94%
“…Other adnexal disorders include pilonidal cyst, hidradenitis suppurativa, pseudofolliculitis barbae, keratosis pilaris atrophicans, and primary axillary hyperhidrosis . Where possible, the data for these studies are summarized in Table S3C.…”
Section: Results By Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of KP includes various keratolytics, chemical or mechanical peels, vitamin D3 analogues, topical or systemic retinoids, and laser or light therapy with various clinical outcomes (1)(2)(3)(4). Recently, our study group treated two patients with KP on the extremities with three sessions of a 595-nm pulsed dye laser (PDL), a long-pulsed 755-nm alexandrite laser, and microdermabrasion combination therapy with marked clinical improvements (5).…”
Section: Introductionmentioning
confidence: 96%